Examining supports and barriers to breastfeeding through a socio-ecological lens: a qualitative study - Kailey Snyder; Emily Hulse; Holly Dingman; Angie Cantrell; Corrine Hanson; Danae Dinkel (BMC, 2021)
Abstract Background Early breastfeeding cessation is a societal concern given its importance to the health of mother and child. More effective interventions are needed to increase breastfeeding duration. Prior to developing such interventions more research is needed to examine breastfeeding supports and barriers from the perspective of breastfeeding stakeholders. One such framework that can be utilized is the Socio-Ecological Model which stems from Urie Broffenbrenner's early theoretical frameworks (1973-1979). The purpose of this study was to examine supports and barriers to breastfeeding across environmental systems. Methods A total of 49 representatives participated in a telephone interview in Nebraska, USA in 2019. Interviewees represented various levels of the model, based on their current breastfeeding experience (i.e., mother or significant other) or occupation. A direct content analysis was performed as well as a constant comparative analysis to determine differences between level representatives. Results At the Individual level, breastfeeding is a valued behavior, however, women are hindered by exhaustion, isolation, and the time commitment of breastfeeding. At the Interpersonal level, social media, peer-to-peer, and family were identified as supports for breastfeeding, however lack of familial support was also identified as a barrier. At the community level, participants were split between identifying cultural acceptance of breastfeeding as support or barrier. At the organizational level, hospitals had supportive breastfeeding friendly policies in place however lacked enough personnel with breastfeeding expertise. At the policy level, breastfeeding legislation is supportive, however, more specific breastfeeding legislation is needed to ensure workplace breastfeeding protections. Conclusion Future efforts should target hospital-community partnerships, family-centered education, evidence-based social media strategies and improved breastfeeding legislation to ensure breastfeeding women receive effective support throughout their breastfeeding journey.